Cost Analysis of Volar Plate Fixation Versus Plaster Cast Immobilization for Intra-Articular Distal Radial Fractures. (3rd November 2021) - Selles, C.A.; Mulders, M.A.M.; van Dieren, S.; Goslings, J.C.; Schep, N.W.L.
Abstract : Background: The aim of this study was to compare the cost-effectiveness and cost-utility between plaster cast immobilization and volar plate fixation for acceptably reduced intra-articular distal radial fractures. Methods: A cost-effectiveness analysis was conducted as part of a randomized controlled trial comparing operative (volar plate fixation) with nonoperative (plaster cast immobilization) treatment in patients between 18 and 75 years old with an acceptably reduced intra-articular distal radial fracture. Health-care utilization and use of resources per patient were documented prospectively and included direct medical costs, direct non-medical costs, and indirect costs. All analyses were performed according to the intention-to-treat principle. Results: The mean total cost per patient was 291 (95% bias-corrected and accelerated confidence interval [bcaCI] = −1, 286 to 1, 572) higher in the operative group compared with the nonoperative group. The mean total number of quality-adjusted life-years (QALYs) gained at 12 months was significantly higher in the operative group than in the nonoperative group (mean difference = 0.15; 95% bcaCI = 0.056 to 0.243). The difference in the cost per QALY (incremental cost-effectiveness ratio [ICER]) was 2, 008 (95% bcaCI = −9, 608 to 18, 222) for the operative group compared with the nonoperative group, which means that operative treatment is more effective but also more expensive. Subgroup analysis including only patients with a paid job showed that the ICER was −3, 500 per QALY for the operative group with a paid job compared with the nonoperative group with a paid job, meaning that operative treatment is more effective and less expensive for patients with a paid job. Conclusions: The difference in QALYs gained for the operatively treated group was equivalent to an additional 55 days of perfect health per year. In adult patients with an acceptably reduced intra-articular distal radial fracture, operative treatment is a cost-effective intervention, especially in patients with paid employment. Operative treatment is slightly more expensive than nonoperative treatment but provides better functional results and a better quality of life. Level of Evidence: Economic and Decision Analysis Level I . See Instructions for Authors for a complete description of levels of evidence.